Internet Behavior Preferences Predict Pathological Internet Use: A Latent Profile Analysis - Chen, Jiangtao; Liu, Jinmeng; Zhao, Gai; Kong, Fanchang (Frontiers in Psychology, 2021)
Recent research into the underlying structure of pathological Internet use (PIU) has produced considerable debate among academics, among which a new person-centered approach to studying pathological Internet use has recently gathered support but produced mixed results. The present study used latent profile analysis (LPA) to estimate the types of PIU in a large sample of college students (n = 1,400, aged 17–25 years). Participants provide information on demographics, PIU, and Internet behavior preferences. The adolescent pathological Internet use (APIU), served as the basis of LPA, was used to search for subgroups representing participants with PIU. LPA identified PIU classes and regressions identified psychological predictors of class membership. Participants were classified as pathological users, pathological-tendency users, preferential users, and ordinary Internet users. Compared to pathological Internet users, lower Internet gaming and communication preference were associated with pathological-tendency users, preferential users and ordinary Internet users. Distinct types of college students belong to each PIU class, suggesting that individual differences be incorporated in prevention efforts.